Pengaruh Servant Leadership Dan Spiritual Leadership Terhadap Motivasi Kerja Pegawai Pada Kantor UPTD PPD Kabupaten Kepahiang - Nelli Asvriana; Fahrudin JS Fahreke; I Wayan Dharmayana (Student Journal of Business and Management, 2022)
Abstract : Work motivation has an important role in an organization, because with high work motivation it will increase work productivity for employees in carrying out their duties. The factors that influence work motivation are: human needs, compensation factors, communication factors, leadership factors, training factors, factors achievement. The leadership factor is one of the factors that affect the morale of the employees. The aims of this study are 1) To examine the effect of servant leadership and spiritual leadership together on employee motivation at the UPTD PPD office in Kepahiang Regency. 2) To examine the influence of servant leadership on employee work motivation at the UPTD PPD office in Kepahiang Regency. 3) To examine the influence of spiritual leadership on employee work motivation at the UPTD PPD office in Kepahiang Regency. The conclusions in this study are as follows: 1) The results of the study prove that servant leadership and spiritual leadership have a positive and significant effect on work motivation at the UPTD PPD Office, Kepahiang Regency by 48.3%, meaning that by applying servant leadership and spiritual leadership styles at the UPTD PPD Office Kepahiang Regency can increase work motivation and if the leadership always pays attention to and applies servant leadership and spiritual leadership styles, work motivation will continue to increase. 2) The results of the study prove that servant leadership has a positive and significant effect on work motivation at the UPTD PPD Office in Kepahiang Regency by 22.8%, meaning that by applying the servant leadership style at the UPTD PPD Kepahiang Office, it can increase work motivation and if the leadership always pays attention and applies this style. servant leadership, work motivation will continue to increase. 3) The results of the study prove that spiritual leadership has a positive and significant effect on work motivation at the UPTD PPD Office in Kepahiang Regency by 54.3%, meaning that by applying the spiritual leadership style at the UPTD PPD Kepahiang Office, it can increase work motivation and if the leadership always pays attention and applies this style. spiritual leadership, work motivation will continue to increase. Keywords: Servant Leadership, Spiritual Leadership, Work Motivation Abstrak : Tujuan penelitian ini adalah 1) Untuk menguji pengaruh servant leadership dan spiritual leadership secara bersama-sama terhadap motivasi kerja pegawai pada kantor UPTD PPD Kabupaten Kepahiang. 2) Untuk menguji pengaruh servant leadership terhadap motivasi kerja pegawai pada kantor UPTD PPD Kabupaten Kepahiang. 3) Untuk menguji pengaruh spiritual leadership terhadap motivasi kerja pegawai pada kantor UPTD PPD Kabupaten Kepahiang. Penelitian ini dilakukan dengan pendekatan kuantitatif, Populasi pegawai pada kantor UPTD PPD Kabupaten Kepahiang. Teknik sampling yang digunakan adalah nonprobability sampling dengan sampling jenuh kepada seluruh pegawai pada Kantor UPTD PPD Kepahiang yang tidak mempunyai jabatan struktural tertentu sebanyak 135 pegawai. Hasil penelitian membuktikan bahwa servant leadership dan spiritual leadership berpengaruh secara positif dan signifikan terhadap motivasi kerja di Kantor UPTD PPD Kabupaten Kepahiang sebesar 48.3 % artinya bahwa dengan menerapkan gaya servant leadership dan spiritual leadership di Kantor UPTD PPD Kabupaten Kepahiang dapat meningkatkan motivasi kerja dan jika pimpinan selalu memperhatikan dan menerapkan gaya servant leadership dan spiritual leadership maka motivasi kerja akan terus meningkat. 2) Hasil penelitian membuktikan bahwa servant leadership berpengaruh secara positif dan signifikan terhadap motivasi kerja di Kantor UPTD PPD Kabupaten Kepahiang sebesar 22.8 % artinya bahwa dengan menerapkan gaya servant leadership di Kantor UPTD PPD Kabupaten Kepahiang dapat meningkatkan motivasi kerja dan jika pimpinan selalu memperhatikan dan menerapkan gaya servant leadership maka motivasi kerja akan terus meningkat. 3) Hasil penelitian membuktikan bahwa spiritual leadership berpengaruh secara positif dan signifikan terhadap motivasi kerja di Kantor UPTD PPD Kabupaten Kepahiang sebesar 54.3 % artinya bahwa dengan menerapkan gaya spiritual leadership di Kantor UPTD PPD Kabupaten Kepahiang dapat meningkatkan motivasi kerja dan jika pimpinan selalu memperhatikan dan menerapkan gaya spiritual leadership maka motivasi kerja akan terus meningkat. Kata Kunci : Spiritual Leadership, Servant Leadership, Motivasi Kerja